The Effect of Using Edpuzzle-Based Video in Electrolyte and Nonelectrolyte Solutions Learning on Student Learning Outcomes - Dio Ganda Putra Damanik; Johnsen Harta (Universitas Pendidikan Mandalika, 2023)
The limitation of using learning media atSMAN 1 Kalasan causes the learning of electrolyte and nonelectrolyte solutions to be less interesting and less effective. Therefore, learning can be supported by attractive video design in the form of Edpuzzle which hasthe potential to build better learning processes and outcomes. This research aims to evaluate the effect of Edpuzzle-based video implementation in electrolyte and nonelectrolyte solutions lessons on student learning outcomes. In form ofa Quasi-Experimental Design, this research was carried out by One-Group Pretest-Posttest Design. The research sample is students of X MIPA 2 that selected by simple random sampling. The instruments used were validation sheets, lesson plans, pretest, and posttest items, questions in Edpuzzle video, an observation sheet of Edpuzzle-based video implementation, and a students’ response questionnaire. Research data were analyzed by SPSS 25, Aiken’s Statistics, and descriptively. The results showed that using Edpuzzle-based video had an influence on students’ learning outcomes that support by Sig value. (2-tailed) < 0.05 andthe average of N-Gain is 0.8 (high). The average post-test is 96.7 (excellent). During Edpuzzle video implementation on learning, the cognitive achievement of C1, C2, and C3respectively levelcompleted are 100%, 100%, and 91.66%, while, C4 and C5 are respectively 22.22% and 41.66%, In addition, the achievement of learning outcomes indicator is also supported by observation for psychomotor and affective domains, with a respectively average scores 96.06% and 95.48%. Edpuzzle-based video can be used as support for electrolyte and nonelectrolyte learning in senior high school.